Optimization of Services in Workshops Thanks to The Use of a Website-Based Information System - Wahyuni, Novira; Marwa, Safni; Rusnedy, Hidayati (Journal of Engineering Science and Technology Management, 2026)
The Berkat Yakin Workshop still implements a manual service and data recording system, causing various problems such as difficulties in managing service data, service history, and uncertainty in estimating time and costs for customers. This research aims to optimize services at the Yakin Blessing Workshop through the development of a website-based information system. The system development method used is the Framework for the Application of System Thinking (FAST) with stages of scope definition, problem analysis, requirements analysis, logical design, physical design, construction and testing, and installation and delivery. The system was developed using the Laravel framework with MySQL databases and Unified Modeling Language (UML) modeling. The system test was carried out using Blackbox Testing with the Equivalence Partitioning technique. The results of the study show that the website-based information system is able to improve the operational efficiency of the workshop, make it easier to manage service and customer data, and provide convenience for customers in booking services and obtaining information on estimated costs and processing time. Thus, the system developed is considered to be able to improve the quality of service at the Yakin Blessing Workshop.